Sign change of the extended s -wave pairing vertex in the dynamic Hubbard model: A quantum Monte Carlo study - Bouadim, K.; Enjalran, Matthew; Hébert, F.; Batrouni, G. George; Scalettar, Richard T. (Physical Review B, 2008)
The "dynamic" Hubbard Hamiltonian describes interacting fermions on a lattice whose on-site repulsion is modulated by a coupling to a fluctuating bosonic field. We investigate one such model, introduced by Hirsch, using the determinant quantum Monte Carlo method. Our key result is that the extended s -wave pairing vertex, repulsive in the usual static Hubbard model, becomes attractive as the coupling to the fluctuating Bose field increases. The sign problem prevents us from exploring a low enough temperature to see if a superconducting transition occurs. We also observe a stabilization of antiferromagnetic correlations and the Mott gap near half-filling, and a near linear behavior of the energy as a function of particle density which indicates a tendency toward phase separation. © 2008 The American Physical Society.
Keywords: dept.phy